THE REDUCED PHASE-SPACE OF SPHERICALLY SYMMETRICAL EINSTEIN-MAXWELL THEORY INCLUDING A COSMOLOGICAL CONSTANT - Thiemann, Thomas (Nuclear Physics B, 1995)
We investigate several conceptual and technical details that might be of interest for full (3 + 1) gravity. We use the new canonical variables introduced by Ashtekar, which simplifies the analysis tremendously.